Sistema de informações geográficas de baixo custo para apoio à gestãode bacias hidrográficas - Moises Junio Silveira (2010)
This paper presents a methodology for creating a geographic information system plataform and free public domain data to be instrumental in watershed management. As a case study isapproached river basin St John the main data souces are letters from IBGE and images ASTER/MDT, where processed on the platforms gvSIG, SPRING TRACKMAKER and giving rise to information that characterize the river basin ST John are regarding their water, morphological, social and administrative. This information feeds a database system that ismanaged by PostGreSQL/PortGIS, connected to the system of GIS gvSIG where are the jobs and appointments made by users. The methodology of work comes down to selecting, processing and conversion of information, creation of a special database and integration ofinformation from the same, connecting to a database system for processing of georeferenced data and compiling a dictionary os data showing the GIS metadata for future updates. The following is described and illustrated all the steps for implementing the proposedmethodology, as well as the source of primary data and software necessary for development of GIS SAOJOAO. At the end of the paper presents a graphical interface system and some examples of applications related to water resources management. For a better use of GIS SAOJOAO the end user must seek new knowled about yhe system gvSIG, because it has tools for creating maps, analyzes, measures and update the database.